Reconstruction of Islamic Religious Education in Addressing the Challenges of Digital Disruption: A Systematic Literature Review - Hairunisa, Nur (PT. Anagata Sembagi Education, 2026)
The rapid acceleration of digital transformation has significantly reshaped educational paradigms, shifting from traditional teacher-centered models toward active, technology-based, and learner-centered approaches. Islamic Religious Education (IRE) faces unique challenges in balancing digital adaptation with the preservation of spiritual and moral values. This study aims to systematically analyze and reconstruct the paradigmatic foundations, challenges, and strategic directions of IRE in the era of digital disruption. Employing a qualitative design through a Systematic Literature Review (SLR), this research analyzed 42 peer-reviewed journal articles published between 2020 and 2025. The review process followed PRISMA procedures and applied TCCM and ADO frameworks for thematic categorization and conceptual synthesis. The findings indicate that dominant research themes include digital pedagogical transformation, curriculum reconstruction, and teacher digital competence, while integrative theoretical model development remains limited. The study identifies significant gaps in harmonizing sacred knowledge with critical digital literacy and ethical moderation. Consequently, this research proposes a multidimensional reconstruction framework encompassing digital curriculum integration, enhancement of teacher digital-spiritual competence, participatory learning models, and the institutionalization of Islamic digital ethics. The study concludes that Islamic Religious Education must adopt an integrative and proactive paradigm to remain relevant, authentic, and transformative in responding to ongoing digital disruption.